Дослідження надземної частини буряків як джерела харчового протеїну - Сімахіна, Галина Олександрівна; Солодко, Лілія Миколаївна (My University, 2014)
У статті наведено результати експериментальних досліджень білкового складу надземної частини буряків і показано перспективи її використання як джерела харчового протеїну. The article represents the results of experimental researches on amino-acid compound of overground part of beets and shows the perspectives of its usage as a source of food protein. The fractional composition of proteins has been studied. It has been elucidated that such proteins contain mostly water-soluble and salt-soluble factions. This characteristic promotes their better balance on amino-acid compound.
Keywords: цукровий буряк; кормовий буряк; столовий буряк; білки; протеолітичні ферменти; sugar beet; forage beet; red beet proteins; proteolythic enzymes; fractioning; кафедра технології оздоровчих продуктів